2019
DOI: 10.3390/ijms20123033
|View full text |Cite
|
Sign up to set email alerts
|

Glucosylsphingosine (lyso-Gb1) as a Biomarker for Monitoring Treated and Untreated Children with Gaucher Disease

Abstract: The role of glucosylsphingosine (lyso-Gb1), a downstream metabolic product of glucosylceramide, for monitoring treated and untreated children with Gaucher disease (GD) has not yet been studied. We reviewed the clinical charts of 81 children (<18 years), 35 with mild type 1 GD (GD1), 34 with severe GD1 and 12 with type 3 GD (GD3), followed at Shaare Zedek Medical Center between 2014–2018. Disease severity for GD1 was based on genotypes. Forty children (87%) with severe GD1 and GD3 received enzyme replacement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
58
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 19 publications
4
58
0
2
Order By: Relevance
“…Four recent studies found that lyso-Gb1 measurement in dried blood spots is useful for monitoring patients with GD [ 126 , 127 , 128 ]. Among 103 untreated adult patients with type 1 GD who were followed up over a median of 20 years, the median lyso-Gb1 in dried blood spots at the last visit was 108.5 ng/mL (normal, <8 ng/mL) [ 126 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Four recent studies found that lyso-Gb1 measurement in dried blood spots is useful for monitoring patients with GD [ 126 , 127 , 128 ]. Among 103 untreated adult patients with type 1 GD who were followed up over a median of 20 years, the median lyso-Gb1 in dried blood spots at the last visit was 108.5 ng/mL (normal, <8 ng/mL) [ 126 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lyso-Gb1 concentrations negatively correlated with platelet count in non-splenectomized patients but not with any other GD-related parameter [ 126 ]. In a separate study, up to 10 years of lyso-Gb1 data (measured in plasma and dried blood spots) from 292 patients enrolled in a single center participating in the Gaucher Outcome Survey registry were analyzed with respect to treatment outcomes [ 127 ]. Most patients had the homozygous N370S genotype and received relatively low doses of ERT [ 127 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are used as an indicator of disease severity and its response to therapy. Currently, glucosylsphingosine (lyso-Gb1) is used as a more effective alternative to chitotriosidase and CCL18 [113,114].…”
Section: Gaucher Diseasementioning
confidence: 99%
“…The plasma biomarker glucosylceramide (GlcCer), and ceramide ratios, have been used in combination with ERT treatment for this condition, with levels significantly decreasing with corresponding treatments in GD 1 patients [44]. Moreover, glucosylsphingosine has also been determined to be a biomarker in dried blood spots (DBS) from children with GD 1 and 3 diseases [47]. Glucosylsphingosine has also proven to have diagnostic potential in other LSDs, further validating its potential as a generalised LSD-specific biomarker [45,46].…”
Section: Gaucher Diseasementioning
confidence: 99%